The final obstacle to successful pre‐clinical xenotransplantation?. (25th June 2020) - Yamamoto, Takayuki; Hara, Hidetaka; Iwase, Hayato; Jagdale, Abhijit; Bikhet, Mohamed H.; Morsi, Mahmoud.A.; Cui, Yehua; Nguyen, Huy Q.; Wang, Zheng‐Yu; Anderson, Douglas J.; Foote, Jeremy; Schuurman, Henk‐Jan; et al.
Abstract: Genetically engineered pigs are now available for xenotransplantation in which all three known carbohydrate xenoantigens, against which humans have natural antibodies, have been deleted (triple‐knockout [TKO] pigs). Furthermore, multiple human transgenes have been expressed in the TKO pigs, all of which are aimed at protecting the cells from the human immune response. Many human sera demonstrate no or minimal antibody binding to, and little or no cytotoxicity of, cells from these pigs, and this is associated with a relatively low T‐cell proliferative response. Unfortunately, baboons and other Old World NHPs have antibodies against TKO pig cells, apparently directed to a fourth xenoantigen that appears to be exposed after TKO. In our experience, most, if not all, humans do not have natural antibodies against this fourth xenoantigen. This discrepancy between NHPs and humans is providing a hurdle to successful translation of pig organ transplantation into the clinic, and making it difficult to provide pre‐clinical data that support initiation of a clinical trial. The potential methods by which this obstacle might be overcome are discussed. We conclude that, whatever currently available genetically engineered pig is selected for the final pre‐clinical studies, this may not be the optimal pig for clinical trials.